Pengaruh Komitmen dan Pola Kerja Terhadap Kinerja Pada Rumah Sakit Delima Asih Sisma Medika - Aulia Wardatul Umah; Eman Sulaeman (Peneliti.net, 2023)
The success of an organization, both large and small, is not solely determined by the available natural resources, but much is determined by the quality of human resources whose role is to plan, implement and control the organization concerned. However, the continuity of development currently being carried out in our country can only be maintained if the quality of existing human resources receives serious attention from the government. A hospital is a health service institution that provides comprehensive individual health services that provide inpatient, outpatient and emergency services. Along with the increase in education and social economic growth in society and in welcoming the era of globalization, the understanding of health has also increased, this is indicated by the increasing criticality of the community towards the services provided by a hospital, it is necessary to improve efforts, including oriented to patients including patient satisfaction. patients for hospital services. The research method used is a quantitative descriptive method, namely analyzing HR data and information obtained from the hospital. The sampling technique used in this study, namely snowball sampling, is a sampling technique that is initially carried out in small quantities, then the first selected sample is asked to choose the next sample, which in the end the number of samples will increase, like a rolling snowball that gets bigger and bigger. The research instrument was a questionnaire which was compiled based on the indicators of the research variables. The type of data used in this study is quantitative data, namely data obtained in the form of numbers that can be calculated relating to the problem under study, namely hospital HR reports and qualitative data, namely data that cannot be counted or is not in the form of numbers obtained from the results interview. The purpose of this study is to determine the performance of hospital human resources.